2020
DOI: 10.22219/jes.v5i1.11400
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Financing Scheme Effect on Non-Performing Financing Asset at Islamic Banks In Indonesia

Abstract: This research aims to identify the impact of financing contracts on the risks confronted by Islamic banks measured by Non-Performing Financing (NPF). The data indicate that the value of NPF tends to annually increase along with a value close to the maximum limit set by Bank Indonesia (BI). The data of this study utilized secondary data in the form of monthly time series data in the period of January 2014 to December 2017 and cross-section data from the two types of Islamic Banking (Bank Usaha Syariah and Unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 10 publications
0
8
1
3
Order By: Relevance
“…This study is in line with the research results of Akram & Rahman (2018) and Kuswahariani et al (2020), which revealed that financing management has a good impact on reducing Islamic bank financing risk. The results of this study are different from the results of studies from Rahmah & Armina (2020) and Aprilianto (2020), who revealed that FDR and financing with musyarakah profit-sharing schemes affect the increased risk of financing.…”
Section: Discussioncontrasting
confidence: 99%
“…This study is in line with the research results of Akram & Rahman (2018) and Kuswahariani et al (2020), which revealed that financing management has a good impact on reducing Islamic bank financing risk. The results of this study are different from the results of studies from Rahmah & Armina (2020) and Aprilianto (2020), who revealed that FDR and financing with musyarakah profit-sharing schemes affect the increased risk of financing.…”
Section: Discussioncontrasting
confidence: 99%
“…Artinya pembiayaan dengan akad mudharabah berpotensi meningkatkan jumlah pembiayaan bermasalah. Sementara studi yang dilakukan oleh Warninda et al, (2019) juga membuktikan bahwa pembiayaan dengan akad musyarakah memiliki risiko, karena berpengaruh positif terhadap pembiayaan bermasalah (Aprilianto, 2020). Demikian halnya dengan studi yang dilakukan oleh Afzal & Hassan (2018) yang juga menunjukkan bahwa faktor risiko adalah salah satu penghambat minimnya penerapan akad mudharabah dalam pembiayaan bank syariah di Pakistan.…”
Section: Sumber: Ojk 2019bunclassified
“…Dengan demikian penyaluran pembiayaan dengan prinsip bagi hasil tidak akan berdampak pada pembiayaan bermasalah, jika syarat-syarat standar yang ditentukan oleh Otoritas Jasa Keuangan dapat dipenuhi. Secara konsep pembiayaan dengan prinsip bagi hasil memang memiliki risiko yang tinggi (Putra, 2019;(Warninda et al, 2019;Aprilianto, 2020). Oleh karena tingginya risiko dalam pembiayaan dengan prinsip bagi hasil, menjadi salah satu penyebab rendahnya jumlah penyaluran pembiayaan dengan prinsip bagi hasil (Afzal & Hassan, 2018).…”
Section: Landasan Teoriunclassified
See 1 more Smart Citation
“…The existence of Islamic banks in addition to conventional banks indicates the start of a new era in the national banking legal system (Kasri, & Kassim, 2009;Ahmad, & Luo, 2010;Farook, Hassan, & Lanis, 2011;Abdullah, Percy & Stewart, 2015), namely the era of the dual banking system. Furthermore, the government has also issued a new regulation specifically regulating sharia banking (Ahmad, & Hassan, (2007;Nicholls, 2010;Alam, Zainuddin, & Rizvi, 2019;Mahdi, 2019;Aprilianto, 2020), namely through the Law of the Republic of Indonesia Number 21 of 2008 concerning Sharia Banking. The existence of support for Islamic banking both from the Muslim community, religious institutions and the government, triggered the development of Islamic banking which was quite rapid (Venardos, 2012;Hanif, 2014;Kammer, et.…”
Section: Introductionmentioning
confidence: 99%